Camera with automatic data compression factor selection - SUZUKI; MASAHIRO (1995)
Image processing system for a camera which automatically selects a data compression factor. The system converts an image of a photographic subject into digital data, compresses the digital data and stores it on a recording medium. An imaging unit first converts light from a photographic subject into analog image signals which are processed by a signal processing unit, A/D converted and temporarily stored in a buffer memory. A data compression factor is automatically selected for data compression processing based upon components of signals extracted from analog image data output from the signal processing unit. Data compression processing is then performed at high speed on the image data stored in the buffer memory according to the selected compression factor.